The development of guided-inquiry based student worksheets integrated with Islamic values on environmental pollution material - Dayana Fazira; Ummi Nur Afinni Dwi Jayanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Guided inquiry-based student worksheets (LKPD) that are integrated with Islamic values are still rarely developed. This research was conducted with the aim of developing LKPD, as well as testing validity, practicality and effectiveness in classroom learning. The method used is Research and Development (R&D) 4D model. Data was collected using validation sheets by media experts, materials, Islamic values material, biology teacher response questionnaires and class X MIA MAS Madinatussalam Deli Serdang students. The results of the study obtained a score of 96.15% in the "very valid" category for the media feasibility test, a score of 100% in the "very valid" category for the material feasibility test, a score of 82.86% in the "valid" category for the material feasibility test on Islamic values. The practicality test scored 96.6% (teacher response), and 89.37% (student response) in the practical category. The effectiveness test got an average N-Gain score of 0.599 with a "moderate" classification and was declared effective in increasing student learning outcomes and environmental care attitudes with a percentage of 92.12%. This LKPD can facilitate learning outcomes and instills the practice of caring for the environment which is integrated with Islamic values which will form a form of faith and gratitude to Allah, the creator of the universe, as well as being the basis for the development of other LKPD that integrates Islamic values.Abstrak Lembar kerja peserta didik (LKPD) berbasis inkuiri terbimbing yang terintegrasi dengan nilai-nilai Islam masih jarang dikembangkan. Penelitian ini dilakukan dengan tujuan untuk mengembangkan LKPD, serta menguji kevalidan, kepraktisan dan keefektifan dalam pembelajaran dikelas. Metode yang digunakan yaitu Research and Development (R&D) model 4D. Data dikumpulkan menggunakan lembar validasi oleh ahli media, materi, materi nilai-nilai Islam, angket respon guru biologi dan peserta didik kelas X MIA MAS Madinatussalam Deli Serdang. Hasil penelitian didapatkan skor 96,15% dengan kategori “sangat valid” untuk uji kelayakan media, skor 100% dengan kategori “sangat valid” untuk uji kelayakan materi, skor 82,86% dengan kategori “valid” untuk uji kelayakan materi nilai Islam. Uji kepraktisan mendapat skor 96,6% (respon guru), dan 89,37 % (respon peserta didik) dengan kategori praktis. Uji keefektifan mendapat skor rata-rata N-Gain sebesar 0,599 dengan klasifikasi “sedang” dinyatakan efektif meningkatkan hasil belajar dan sikap peduli lingkungan siswa dengan persentase sebesar 92,12%. LKPD ini dapat memfasilitasi hasil belajar dan menanamkan pengamalan sikap peduli lingkungan yang diintegrasikan dengan nilai-nilai Islam akan membentuk wujud rasa iman dan bersyukur kepada Allah pencipta alam semesta, serta menjadi dasar pengembangan LKPD terintegrasi nilai Islam lainnya.